The real wealth of nations - Eyre, S. R. (St. Martin's Press, 1978)
This book The Real Wealth of Nations because it shows that our most important economic assets are not financial - that the real wealth of nations consists of the contributions of people and our natural environment....To address the needs of our world today, we have to bring together knowledge from many areas. It is a book for everyone who wants a better life and a better world, and is looking for practical tools to realize these goals.